Acute shock efficacy of the subcutaneous implantable cardioverter‐defibrillator according to the implantation technique. (16th May 2021) - Francia, Pietro; Adduci, Carmen; Angeletti, Andrea; Ottaviano, Luca; Perrotta, Laura; De Vivo, Stefano; Bongiorni, Maria Grazia; Migliore, Federico; Russo, Antonio Dello; De Filippo, Paolo; Caravati, Fabrizio; Nigro, Gerardo; et al.
Abstract: Background: The traditional technique for subcutaneous implantable cardioverter defibrillator (S‐ICD) implantation involves three incisions and a subcutaneous (SC) pocket. An intermuscular (IM) 2‐incision technique has been recently adopted. Aims: We assessed acute defibrillation efficacy (DE) of S‐ICD (DE ≤65 J) according to the implantation technique. Methods: We analyzed consecutive patients who underwent S‐ICD implantation and DE testing at 53 Italian centers. Regression analysis was used to determine the association between DFT and implantation technique. Results: A total of 805 patients were enrolled. Four groups were assessed: IM + 2 incisions ( n  = 546), SC + 2 incisions ( n  = 133), SC + 3 incisions ( n  = 111), and IM + 3 incisions ( n  = 15). DE was ≤65 J in 782 (97.1%) patients. Patients with DE ≤65 J showed a trend towards lower body mass index (25.1 vs. 26.5; p  = .12), were less frequently on antiarrhythmic drugs (13% vs. 26%; p  = .06) and more commonly underwent implantation with the 2‐incision technique (85% vs. 70%; p  = .04). The IM + 2‐incision technique showed the lowest defibrillation failure rate (2.2%) and shock impedance (66 Ohm, interquartile range: 57–77). On multivariate analysis, the 2‐incision technique was associated with a lower incidence of shock failure (hazard ratio: 0.305; 95% confidence interval: 0.102–0.907; p  = .033). Shock impedance was lower with the IM than with the SC approach (66 vs. 70 Ohm p  = .002) and with the 2‐incision than the 3‐incision technique (67 vs. 72 Ohm; p  = .006). Conclusions: In a large population of S‐ICD patients, we observed a high defibrillation success rate. The IM + 2‐incision technique provides lower shock impedance and a higher likelihood of successful defibrillation.